Carbon nanotube-reinforced siloxane-PMMA hybrid coatings with high corrosion resistance - Hammer, Peter [UNESP]; Dos Santos, F. C. [UNESP]; Cerrutti, B. M. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier, 2013)
Siloxane-polymethyl methacrylate hybrid films containing functionalized multiwall carbon nanotubes (CNTs) were deposited by dip-coating on carbon steel substrates from a sol prepared by radical polymerization of methyl methacrylate and 3-methacryloxy propyl-trimethoxysilane, followed by hydrolytic co-polycondensation of tetraethoxysilane. The correlation between the structural properties and corrosion protection efficiency was studied as a function of the molar ratio of nanotubes carbon to silicon, varied in the range between 0.1% and 5%. 29Si nuclear magnetic resonance and thermogravimetric measurements have shown that hybrids containing carbon nanotubes have a similar degree of polycondensation and thermal stability as the undoped matrix and exhibit and excellent adhesion to the substrate. Microscopy and X-ray photoelectron spectroscopy results revealed a very good dispersion of carbon nanotubes in the hybrid matrix and the presence of carboxylic groups allowing covalent bonding with the end-siloxane nodes. Potentiodynamic polarization curves and electrochemical impedance spectroscopy results demonstrate that CNTs containing coatings maintain the excellent corrosion protection efficiency of the hybrids, showing even a superior performance in acidic solution. The nanocomposite structure acts as efficient corrosion barrier, increasing the total impedance by 4 orders of magnitude and reducing the current densities by more than 3 orders of magnitude, compared to the bare steel electrode. © 2013 Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Corrosion protection; Electrochemical properties; Hybrid coatings; Photoelectron spectroscopy; Sol-gel process; Acidic solutions; Bare steel; Carbon steel substrates; Carboxylic group; Corrosion barriers; Covalent bonding; Dip coating; Functionalized; Hybrid coating; Hybrid film; Hybrid matrix; Molar ratio; Nano-composite structure; Orders of magnitude; Polymerization of methyl methacrylate; Potentiodynamic polarization curves; Protection efficiency; Similar degree; Thermogravimetric measurement; Carbon steel; Coatings; Corrosion resistance; Electrochemical impedance spectroscopy; Esters; Photoelectrons; Polycondensation; Polymethyl methacrylates; Sols; Substrates; X ray photoelectron spectroscopy